Student Awareness of Social Practices by Using Reading Strategies Through Blogs - Puerto, Paola Yesenia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper reports a qualitative action study carried out with learners from English Level 2 from the International Languages Institute at a public university in the city of Duitama, Colombia. This research arose from a problem reported in a diagnostic survey, which showed the development of reading activities to be monotonous, having scarce knowledge, and using limited reading strategies. Video recording extracts, student blogs and an open-ended questionnaire reported that the use of blogs promotes reading as a meaningful activity. Likewise, the use of strategies (making connections, asking questions, predictions, and imagery) empowered the students to interpret their knowledge and their world. In the same way, reading from blogs revealed reflections, experiences, and personal points of view to challenge and make sense of attitudes, situations, and progress in the social practices of individual students. Five workshops were designed and implemented by adopting the Cognitive Academic Language Learning Approach (CALLA) as a model to guide students in constructing their process as conscious readers.